2017
DOI: 10.1111/nph.14542
|View full text |Cite
|
Sign up to set email alerts
|

A new proteinaceous pathogen‐associated molecular pattern (PAMP) identified in Ascomycete fungi induces cell death in Solanaceae

Abstract: Pathogen-associated molecular patterns (PAMPs) are detected by plant pattern recognition receptors (PRRs), which gives rise to PAMP-triggered immunity (PTI). We characterized a novel fungal PAMP, Cell Death Inducing 1 (RcCDI1), identified in the Rhynchosporium commune transcriptome sampled at an early stage of barley (Hordeum vulgare) infection. The ability of RcCDI1 and its homologues from different fungal species to induce cell death in Nicotiana benthamiana was tested following agroinfiltration or infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 84 publications
2
49
0
Order By: Relevance
“…Based on current knowledge, BAK1 and SOBIR1 participate solely in signaling mediated by LRR receptors, but not receptors with other types of ectodomains such as LysM-receptors or lectin receptor kinases 53 , 54 . Recently, multiple novel MAMPs were identified that require BAK1 or both BAK1 and SOBIR1 45 , 55 , indicating that the corresponding receptors may belong to the LRR class. Moreover, the recognition of certain MAMPs is restricted in Solanaceous plants 29 , 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on current knowledge, BAK1 and SOBIR1 participate solely in signaling mediated by LRR receptors, but not receptors with other types of ectodomains such as LysM-receptors or lectin receptor kinases 53 , 54 . Recently, multiple novel MAMPs were identified that require BAK1 or both BAK1 and SOBIR1 45 , 55 , indicating that the corresponding receptors may belong to the LRR class. Moreover, the recognition of certain MAMPs is restricted in Solanaceous plants 29 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple novel MAMPs were identified that require BAK1 or both BAK1 and SOBIR1 45 , 55 , indicating that the corresponding receptors may belong to the LRR class. Moreover, the recognition of certain MAMPs is restricted in Solanaceous plants 29 , 55 . Therefore, the silencing of the LRR receptor candidates should be a straightforward approach to identify recognition receptors for each MAMP, which will ultimately lead to improved plant resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This limits the experimental throughput. Furthermore, avoiding this first step of virus inoculum buildup in N. benthamiana may be necessary when testing constructs for the expression of generic cell death-inducing proteins (Lacomme and Santa Cruz, 1999;Tang et al, 2015;Kettles et al, 2018), predicted proteinaceous pathogen-associated molecular patterns (Franco-Orozco et al, 2017), or certain candidate pathogen effector proteins that may be recognized by the corresponding immune receptors in this plant species (Dagvadorj et al, 2017;Kettles et al, 2017). Therefore, we assessed the possibility of delivering the FoMV VOX vector directly into wheat leaves using infiltration with the recAdeficient A. tumefaciens strain COR308 harboring the disarmed pTi derivative plasmid pMP90 and the helper plasmid pCH32, which provide extra copies of the virA and virG genes (Hamilton, 1997), and a corresponding protocol that was claimed to be efficient in delivering BSMV-derived gene-silencing constructs directly to wheat leaves (Panwar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…NbBAK1 or NbSOBIR1 expression was silenced using VIGS, as described previously (Kettles et al, 2017). pTRV2-GFP was used as a control, and tobacco NbBAK1 and NbSOBIR1 expression levels were determined by qRT-PCR analysis as described previously (Franco-Orozco et al, 2017). Briefly, A. tumefaciens strain GV3101 harboring pTRV1, pTRV2-GFP, pTRV2-NbBAK1, or pTRV2-NbSOBIR1 constructs were cultured in Luria-Bertani medium containing 50 mg mL 21 kanamycin and incubated at 28°C for 24 h. Bacteria cells were harvested by centrifugation at 5,000g and washed twice in infiltration buffer (10 mM MgCl 2 and 10 mM MES, pH 5.6), and cell density was adjusted to OD 600 = 0.2.…”
Section: Vigs In N Benthamianamentioning
confidence: 99%